THE DIDACTIC POTENTIAL OF VISUALIZATION OF EDUCATIONAL INFORMATION - Sergey A. Noskov (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The visual needs of society increases in modern conditions, and, arguably, that increase spreads on education. The phenomenon of visualization in various fields of science, culture and education has received a lot of attention up to now. There is insufficient developed of visual methods from the perspective of their application in teaching. The article examines the potential of data visualization in terms of rhenium integration in the educational process. Studies have shown that visualization simplifies the communication process, improves cognitive activity of students, and also allows manage time resources of training session more effectively. The concept of "information design" and its differences from classical verbal and visual information was considered, it analyzed the possibility of using infographics in the preparation of modern specialist.